2016
DOI: 10.18632/oncotarget.9704
|View full text |Cite
|
Sign up to set email alerts
|

Niclosamide sensitizes triple-negative breast cancer cells to ionizing radiation in association with the inhibition of Wnt/β-catenin signaling

Abstract: Triple-negative breast cancer (TNBC) is one of the most difficult breast cancers to treat because there is no targeted treatment, and conventional cytotoxic chemotherapy followed by adjuvant radiation therapy is the standard of care for patients with TNBC. We herein reported that ionizing radiation (IR) induced Wnt3a, LRP6 and β-catenin expression and consequently activated Wnt/β-catenin signaling in TNBC MDA-MB-231, MDA-MB-468 and Hs578T cells. Moreover, depletion of β-catenin by shRNA sensitized TNBC cells t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 48 publications
(55 reference statements)
1
36
0
Order By: Relevance
“…As previously reported, the aberrant expression of Wnt3a was also found in several human malignancies, including glioblastoma [16,17], mammary adenocarcinoma [18,19], colon carcinoma [20], lung cancer [21], prostate cancer [22], malignant mesothelioma [23], esophageal squamous cell carcinoma [24], hepatocellular carcinoma [25][26][27], and melanoma [28]. In these malignant tumors, Wnt3a expression is closely related to tumor growth, metastasis, chemo-/ radio-resistance and maintenance of CSC characteristics.…”
Section: Discussionsupporting
confidence: 63%
“…As previously reported, the aberrant expression of Wnt3a was also found in several human malignancies, including glioblastoma [16,17], mammary adenocarcinoma [18,19], colon carcinoma [20], lung cancer [21], prostate cancer [22], malignant mesothelioma [23], esophageal squamous cell carcinoma [24], hepatocellular carcinoma [25][26][27], and melanoma [28]. In these malignant tumors, Wnt3a expression is closely related to tumor growth, metastasis, chemo-/ radio-resistance and maintenance of CSC characteristics.…”
Section: Discussionsupporting
confidence: 63%
“…Niclosamide is an anti-helminthic drug introduced in the 1950's, and has been used to treat parasitic infections in millions of patients worldwide [8]. It has been shown to effect a number of host cellular signaling pathways, including Wnt [9], Notch [10], mTOR, NF-κB [11], and STAT3 [12]. This broad activity has led to its evaluation as a therapeutic agent for a number of cancers, including breast, colon, ovarian, prostate, and others [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Targeting focal adhesion kinase could provide a potential therapeutic approach for improving radiotherapy sensitivity (42). A recent study has identified that the Wnt/β-catenin signaling pathway serves an important role in the development of radioresistance and the inhibition of Wnt/β-catenin signaling may have significant radiosensitizing effects (26). The current study has revealed pathways that may contribute to the CRT response of rectal cancer and may be potential predictive biomarkers.…”
Section: Discussionmentioning
confidence: 72%
“…With regard to the KEGG pathway enrichment results, the upregulated DE genes in CRT responders were mainly involved in pathways including base excision repair and homologous recombination, while downregulated DE genes in CRT responders were enriched in pathways including the Ras signaling pathway, FoxO signaling pathway, focal adhesion and Wnt signaling pathway. These pathways were also indicated to be highly associated with radiation response (23)(24)(25)(26). The seven hub nodes (TOP2B, MAPK8, DLG4, GCG, NGF, INSR and ARRB2) were associated with the Ras signaling pathway, MAPK signaling pathway and FoxO signaling pathway.…”
Section: Identification Of Crt Response-associated Functions and Pathmentioning
confidence: 92%